Perfomance of Agronomic Characters in Several Wheat Varieties Resulting from Gamma Irradiation - Sri Utami; Dafni Mawar Tarigan; Wan Arfiani Barus; Anggria Lestami (Agrosains : Jurnal Penelitian Agronomi, 2025)
Wheat is a cereal crop that can grow well in tropical areas only at high altitudes. However, the limited area of the highlands means that wheat development is directed at the lowlands, so plant breeding efforts are needed to obtain genotypes that are adaptive in the lowlands, one of which is through gamma ray irradiation. This research aims to identify the performance of agronomic characters of several wheat genotypes resulting from gamma irradiation planted in the lowlands. This study used a Randomized Block Design (RBD) with 2 factors, namely the first factor was wheat variety (Dewata/L, Basribey/I, and G-21/F) and the second factor was irradiation dose (0 Gy, 100 Gy, 200 Gy and 300 Gy). The data analyzed using F test at 5%. The treatment means were further compared and separated by using the Duncan Multiple Range Test (DMRT) at 5%. The research results showed that the wheat variety treatment had a significant effect on plant height and leaf area of wheat, while the gamma ray irradiation treatment and the combination of the two treatments had no significant effect on all parameters observed, but showed diversity in agronomic characters.